Penyuluhan Gizi dan Korelasinya dengan Konsumsi Pangan B2SA Pada KWT Sri Rejeki - Ridha Luthfiah, Hana; Euriga, Epsi; Nalinda, Rika (Education and Talent Development Center of Indonesia, 2025)
This community service activity aims to raise awareness of healthy food consumption based on the B2SA (Diverse, Nutritious, Balanced, and Safe) principles through nutrition-sensitive outreach integrated with home-based farming practices. The target group was members of the Sri Rejeki Women's Farmers Group (KWT) in Giritirto Village, Gunungkidul, Yogyakarta Special Region. Implementation methods included participatory outreach, direct observation, semi-structured interviews, and the distribution of a Likert-based questionnaire. Evaluation results indicated that pest control and the selection of nutrient-rich plant varieties were significantly related to improved consumption patterns of nutritious and balanced foods. However, the correlation with indicators of diverse and safe food consumption remained weak. These findings underscore the importance of an intersectoral approach between agricultural technical education and nutrition education to encourage changes in consumption behavior at the household level. This activity also successfully strengthened women's roles in family food management through capacity building and active participation in the outreach program. Thus, nutrition-sensitive outreach, designed in a participatory and contextual manner, can be an effective empowerment strategy for building sustainable family food security.